2018
DOI: 10.1007/s00214-018-2225-0
|View full text |Cite
|
Sign up to set email alerts
|

The highly excited-state manifold of guanine: calibration for nonlinear electronic spectroscopy simulations

Abstract: A computational protocol based on the complete and restricted active space self-consistent field (CASSCF/RASSCF) methods and their second-order perturbation theory extensions (CASPT2/RASPT2) is employed to benchmark the highly excited state manifold of the DNA/RNA canonical purine nucleobase guanine in vacuo. Several RASPT2 schemes are tested, displaying a steady convergence of electronic transition energies and dipole moments upon active space enlargement towards the reference values. The outcome allows calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
(88 reference statements)
1
11
0
Order By: Relevance
“…54,55 Additional computations averaging over the lowest-lying 30 electronic doublet states were carried out on top of the different minima to evaluate the excited state absorption signals. 56,57 Our simulations of these spectral signals assume that excited state absorptions of the individual 2 n + O and 2 π + states are dominated by the electronic structure at their corresponding minima, 58,59 thus neglecting the time-evolution of the system and its lineshape as their simulation requires more sophisticated approaches that are out of the scope of the present study. [60][61][62][63] The CAS state interaction method 64 was employed to evaluate transition dipole moments and oscillator strengths and the energies were corrected with the standard (single-state) CASPT2 formulation with an IPEA shift of 0.0.…”
Section: Computational Detailsmentioning
confidence: 99%
“…54,55 Additional computations averaging over the lowest-lying 30 electronic doublet states were carried out on top of the different minima to evaluate the excited state absorption signals. 56,57 Our simulations of these spectral signals assume that excited state absorptions of the individual 2 n + O and 2 π + states are dominated by the electronic structure at their corresponding minima, 58,59 thus neglecting the time-evolution of the system and its lineshape as their simulation requires more sophisticated approaches that are out of the scope of the present study. [60][61][62][63] The CAS state interaction method 64 was employed to evaluate transition dipole moments and oscillator strengths and the energies were corrected with the standard (single-state) CASPT2 formulation with an IPEA shift of 0.0.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Additional computations averaging over the lowest‐lying 30 electronic doublet states were carried out on top of the different minima to evaluate the excited state absorption signals . The reasoning behind 30 states was so that the CASSCF reference included the intense bright doubly excited states that feature in transient absorption (pump‐probe) experiments, as it has been shown elsewhere . We have assumed that excited state absorptions of the individual 2n+ and 2π+ states are dominated by the electronic structure at their corresponding minima, thus neglecting the time‐evolution of the system and its lineshape, which is costly to simulate and out of the scope of the present study .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Recently, we presented a RASSCF//RASPT2 based protocol for computing reliable transition energies and dipole moments of isolated bio-chromophores and their homo-and heterodimers from rst principles, capable of computing up to 100 electronic states, thereby encompassing the entire IR to NUV regime. [77][78][79][80][81][82][83][84][85][86][87][88] In these studies, we observed that full valence porbital active spaces are oen insufficient to achieve the desired accuracy in conjugated systems. Thus, we have adopted the RASSCF//RASPT2 methodology since it allows increasing the AS size beyond the full valence p-orbital space, treating a signicant part of the dynamic correlation already (variationally) at the RASSCF level.…”
Section: Calculating Spectroscopic Parametersmentioning
confidence: 95%
“…Computations [77][78][79][80][81][82][83][84][85][86][87][88] and ultrafast spectroscopy experiments 17,18,89 have demonstrated that, in single chromophores and small aggregates, PA peaks probing high-lying excited states can provide characteristic spectral signatures in 2DUV maps, besides GSB and SE signals. Since the PA peaks are ubiquitous and very oen overlap with GSB and SE signals, their presence complicates the interpretation of the spectral dynamics, 89,90 making theoretical modeling essential for the analysis of experimental 2DUV maps.…”
Section: Calculating Spectroscopic Parametersmentioning
confidence: 99%